2017
DOI: 10.1371/journal.pntd.0005418
|View full text |Cite
|
Sign up to set email alerts
|

EGF-mediated EGFR/ERK signaling pathway promotes germinative cell proliferation in Echinococcus multilocularis that contributes to larval growth and development

Abstract: BackgroundLarvae of the tapeworm E. multilocularis cause alveolar echinococcosis (AE), one of the most lethal helminthic infections in humans. A population of stem cell-like cells, the germinative cells, is considered to drive the larval growth and development within the host. The molecular mechanisms controlling the behavior of germinative cells are largely unknown.Methodology/Principal findingsUsing in vitro cultivation systems we show here that the EGFR/ERK signaling in the parasite can promote germinative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 53 publications
(87 reference statements)
0
63
0
1
Order By: Relevance
“…A similar type of cytokine receptor interaction appears to involve epidermal growth factor (EGF)-like cytokines and cognate parasite receptors, of which three (EmER, EmERb, EmERc) are expressed by E. multilocularis larvae [3,12]. As recently shown by Cheng et al [13], host-derived EGF is able to stimulate germinative cell proliferation in in vitro cultivated parasite larvae and can stimulate at least one of the parasite EGF-receptors, EmER, when heterologously expressed in Xenopus oocytes. Although the parasite itself expresses several EGF-like molecules [14], which likely act on its EGF receptors, these data indicate that host-EGF could act as an additional stimulus, particularly in response to liver tissue damage as it is inflicted upon entry of the parasite into the host liver [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar type of cytokine receptor interaction appears to involve epidermal growth factor (EGF)-like cytokines and cognate parasite receptors, of which three (EmER, EmERb, EmERc) are expressed by E. multilocularis larvae [3,12]. As recently shown by Cheng et al [13], host-derived EGF is able to stimulate germinative cell proliferation in in vitro cultivated parasite larvae and can stimulate at least one of the parasite EGF-receptors, EmER, when heterologously expressed in Xenopus oocytes. Although the parasite itself expresses several EGF-like molecules [14], which likely act on its EGF receptors, these data indicate that host-EGF could act as an additional stimulus, particularly in response to liver tissue damage as it is inflicted upon entry of the parasite into the host liver [4].…”
Section: Discussionmentioning
confidence: 98%
“…Using in vitro cultivation systems for metacestode vesicles and germinative cells [7-10], we also demonstrated that host insulin fosters parasite development by acting on evolutionarily conserved receptor kinases of the insulin receptor family that are expressed by the metacestode [11]. Evidence has also been obtained that host epidermal growth factor (EGF) stimulates Echinococcus germinative cell proliferation, most probably by acting on parasite receptor tyrosine kinases of the EGF receptor family [12,13]. These studies indicate that the interaction of host-derived hormones and cytokines with corresponding receptors of evolutionarily conserved signalling pathways that are expressed by the parasite may play an important role in AE host-parasite interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively close phylogenetic relationship between helminths and mammalian hosts, it is now clear that they can communicate via evolutionarily conserved signaling systems [66]. Examples are the induction of Epidermal Growth Factor (EGF) signalling in trematodes and cestodes by host derived EGF that binds to evolutionarily conserved EGF receptor kinases [67,68]. We previously demonstrated that also host insulin can stimulate Echinococcus development by acting on evolutionarily conserved insulin signaling systems [69].…”
Section: Discussionmentioning
confidence: 99%
“…The report suggests that the human EGF interacts with helminth EGFR to bring about proliferation of germinal cells and larval growth in the pathogen. In line, inhibition of EGFR with CI‐1033 and BIBW2992 was found to impair the processes and control echinococcosis . The implication of EGFR pathway in regulating other forms of host cell death during infections remains unexplored.…”
Section: Intersection Of Egfr Pathway With Infection‐driven Immune Rementioning
confidence: 99%